2012
DOI: 10.4081/ija.2012.e29
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen fertilization and root growth dynamics of durum wheat for a sustainable production

Abstract: In an area of the Apulian Tavoliere (southern Italy), the effects of three levels of nitrogen fertilization (0, 50 and 100 kg N ha–1) on root development, growth analysis and yield parameters of durum wheat were evaluated. The research was conducted over a four-year period (1994-97). The non-destructive mini-rhizotron method was used to study the root system at stem extension and at the beginning of heading and ripening stages. At the end of tillering and at boot and flowering stages, samples of wheat biomass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
7
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 18 publications
6
7
0
1
Order By: Relevance
“…Enhanced root growth (represented by tap root length and number of primary lateral roots) was more exhibited in "White stem" plants in control than plants supplied with fertilizers. This is in line with studies by De Giorgio and Fornaro [30] who reported that higher N levels can reduce root growth and biomass. In contrast, separate root system morphology studies have demonstrated that total root length and root surface area increased with increased N application (120 Kg/ha) in Oryza sativa [31], and greater root length response can be obtain at N fertilization rate of 127.5 Kg N/ ha compared with either the absence of fertilizer N or the higher rate of 255 Kg N /ha in Zea mays [32].…”
Section: Discussionsupporting
confidence: 93%
“…Enhanced root growth (represented by tap root length and number of primary lateral roots) was more exhibited in "White stem" plants in control than plants supplied with fertilizers. This is in line with studies by De Giorgio and Fornaro [30] who reported that higher N levels can reduce root growth and biomass. In contrast, separate root system morphology studies have demonstrated that total root length and root surface area increased with increased N application (120 Kg/ha) in Oryza sativa [31], and greater root length response can be obtain at N fertilization rate of 127.5 Kg N/ ha compared with either the absence of fertilizer N or the higher rate of 255 Kg N /ha in Zea mays [32].…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, optimum N fertilization had a favorable impact on root growth, which is supported by previous findings that N availability has significant effects on root biomass, production, and mortality [ 68 ]; root elongation [ 17 ]; and higher root-order development and branching [ 69 ]. The application of N fertilizer can also affect water use efficiency by influencing root growth and distribution in the soil [ 70 ], and optimal N fertilization has been shown to enhance root length and diameter [ 12 ], whereas higher and lower N levels have been shown to reduce root growth and biomass [ 71 , 72 , 73 ]. In addition, N fertilization significantly increases the diameter of Larix gmelinii root tips [ 74 ] and the growth, root length, and root diameter of Pongamia pinnata seedlings [ 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…Plants exposed to high nutrient deficiencies exhibited a progressive reduction in TRL [ 23 ]. Therefore, N deficiency can result in a remarkable decrease in length of both first- and second-order lateral roots [ 79 ], a relationship that has been widely confirmed in both annual [ 71 ] and perennial plants [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…Both positive and negative reactions can be found due to differences in the plant and soil nutritional statuses, interactions with site conditions, etc. Significant positive effects have been reported; for example, [35] observed a positive effect of N fertilization on root density in the deep soil layers (except at the highest rate), while [36] found better development of the root system in the deeper soil layers, without nitrogen fertilization. In some experiments, N increased the wheat root density but reduced it at the highest rates [37].…”
Section: Effect Of the Fertilization On The Total Root Length And Roomentioning
confidence: 99%